2016
DOI: 10.4293/jsls.2015.00113
|View full text |Cite
|
Sign up to set email alerts
|

Low vs Standard Pressures in Gynecologic Laparoscopy: a Systematic Review

Abstract: Background:The optimal intraperitoneal pressure during laparoscopy is not known. Recent literature found benefits of using lower pressures, but the safety of doing abdominal surgery with low peritoneal pressures needs to be assessed. This systematic review compares low with standard pneumoperitoneum during gynecologic laparoscopy.Database:We searched Medline, Embase, and the Cochrane Library for randomized controlled trials comparing intraperitoneal pressures during gynecologic laparoscopy. Two authors reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
0
22
0
8
Order By: Relevance
“…2 Lowering the IAP might decrease postoperative pain and the risk of laparoscopy-related complications. 3 However, lowpressure pneumoperitoneum impairs the quality of the surgical field, which can increase the risk of intraoperative complications or conversion to open surgery. 3 The quality of the working space is determined by nonmodifiable factors (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Lowering the IAP might decrease postoperative pain and the risk of laparoscopy-related complications. 3 However, lowpressure pneumoperitoneum impairs the quality of the surgical field, which can increase the risk of intraoperative complications or conversion to open surgery. 3 The quality of the working space is determined by nonmodifiable factors (i.e.…”
mentioning
confidence: 99%
“…3 However, lowpressure pneumoperitoneum impairs the quality of the surgical field, which can increase the risk of intraoperative complications or conversion to open surgery. 3 The quality of the working space is determined by nonmodifiable factors (i.e. patients' obesity, previous pregnancies, or previous abdominal surgery) and by modifiable factors, such as anaesthesia-related factors, IAP, and body position.…”
mentioning
confidence: 99%
“…A recent systematic review did not confirm this reported increase in operating time or blood loss with lower pressure; however, it did raise questions regarding whether the benefit of the observed reduction in postoperative pain could offset the decrease in the quality of surgical conditions [4]. The authors reported an association between lower pressure and increased risk of poorer surgical field visibility (RR 10.31; 95% CI 1.29-82.38).…”
Section: Introductionmentioning
confidence: 95%
“…However, these findings cannot be generalised to gynaecological laparoscopic interventions due to differences in positioning and type of surgical interventions. The few studies that have assessed the use of LP laparoscopy in gynaecological surgery report an overall trend toward reduced postoperative pain levels, but sample sizes were small and inhomogeneous, and distinct outcomes in different pain domains are sparse and rather contradictory . Considering this lack of conclusive data, no sufficient evidence exists for the use of LP laparoscopy in gynaecological interventions in terms of effects on distinct postoperative pain outcomes, laparoscopy‐induced systemic physiological alterations, and safety (intra‐ and postoperative complications).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have assessed the use of LP laparoscopy in gynaecological surgery report an overall trend toward reduced postoperative pain levels, but sample sizes were small and inhomogeneous, and distinct outcomes in different pain domains are sparse and rather contradictory. [15][16][17][18] Considering this lack of conclusive data, no sufficient evidence exists for the use of LP laparoscopy in gynaecological interventions in terms of effects on distinct postoperative pain outcomes, laparoscopy-induced systemic physiological alterations, and safety (intra-and postoperative complications). This study was conducted to compare the use of two different CO 2 pressure levels (15 and 8 mmHg) in patients undergoing laparoscopic hysterectomy for benign uterine pathologies in terms of distinct postoperative pain scores, vegetative laparoscopy-induced alterations, arterial CO 2 pressure (pCO 2 ) levels, safety, and surgical parameters.…”
Section: Introductionmentioning
confidence: 99%